Determination of Water-holding Capacity of Porcine Musculature Based on Released Water Method Using Optimal Load - Joo, Seon-Tea (Korean J Food Sci Anim Resour, 2018)
The purpose of this study was to evaluate the suitability of the released water (RW) method for measuring water-holding capacity (WHC) by pressure and filter-paper absorption within two thin plastic films. One hundred fifty pork loins with considerable variations in WHC (three pork qualities: PSE, pale, soft, and exudative; RFN, reddish-pink, firm, and nonexudative; and DFD, dark, firm, and dry; 50 pork loins in each pork quality group) were used to measure drip loss (DL)% and RW % after applying different loads (1.5, 2.0, 2.5, 3.0 and 3.5 kg). Percentages of DL and RW were significantly (p<0.05) different among pork quality groups. The RW % of 2.5 kg load sample was significantly (p<0.05) higher than that of 2.0 kg or 1.5 kg load sample. However, there were no significant (p>0.05) differences in RW % among 2.5 kg, 3.0 kg, and 3.5 kg load samples for all three pork quality groups. The RW % was highly and positively correlated (r>0.95; p<0.001) with DL %. The highest correlation was observed between DL % and RW % of 2.5 kg load sample (r=0.97; p<0.001). Among all RW loads within each quality groups, the highest correlation between DL % and RW % was observed for 2.5 kg load sample (r=0.43, 0.66, and 0.46 for PSE, RFN and DFD quality groups, respectively, p<0.001). These results imply that applying 2.5 kg load is the best for determination of RW %. It is recommended as a reference method to assess DL % of pork muscles.